Different fatigue behavior between tension-tension and tension-compression of carbon nanotubes reinforced 7055 Al composite with bimodal structure. (30th October 2021) - Bi, S.; Liu, Z.Y.; Xiao, B.L.; Xue, P.; Wang, D.; Wang, Q.Z.; Ni, D.R.; Ma, Z.Y.
Abstract: Understanding the fatigue behavior of Carbon nanotube (CNT) reinforced Al composites (CNT/Al) was of critical importance, for their further application in the aerospace industry. Although CNT could improve the fatigue performance, the fatigue behavior of CNT/Al composites with different structure (e.g. bimodal structure) under different fatigue conditions was still in lacking. In this study, the tension-tension/tension-compression fatigue behaviors of bimodal structure CNT/7055Al composites consisting of ultra-fine grain (UFG) zones rich of CNTs and coarse grain (CG) bands free of CNTs, were investigated and the corresponding damage mechanisms were analyzed. Results indicated that dislocation cells, tangles and subgrains were observed in the CGs, while no obvious dislocation configuration was detected in the UFGs after 10 7 fatigue cycles. Under the tension-tension fatigue condition, the fatigue strength of the composites was increased from 350 MPa to 400 MPa by load transfer effect of CNTs at 10 7 cycles. However, CNTs failed to improve the fatigue strength under the tension-compression fatigue condition due to the failure of the UFG zones rich of CNTs resulting from the high stress amplitude. It was found that strain localization in the CGs was the principal damage mechanism of CNT/7055Al composites. Graphical abstract: Image 1